Suppressor of cytokine signaling-3 expression and its regulation in relation to inflammation in Chronic Obstructive Pulmonary Disease - Tinè, Mariaenrica; Balestro, Elisabetta; Carpi, Sara; Neri, Tommaso; Biondini, Davide; Conti, Maria; Casara, Alvise; Bernardinello, Nicol; Cocconcelli, Elisabetta; Turato, Graziella; Baraldo, Simonetta; Celi, Alessandro; et al. (Frontiers in Immunology, 2024)
The family of Suppressor of Cytokine Signaling (SOCS) act as controllers of the duration and intensity of cytokine function by negatively regulating the JAK-STAT signaling pathway. SOCS role in inflammatory diseases in animal models is well demonstrated. However, its role in the development of human disease is still under investigation. SOCS3 plays an important role in tumor development where its downregulation has been implicated in the pathogenesis of various solid tumors such as triple-negative breast cancer. Aim: To study 1)the expression of SOCS3 in smokers' lungs and its relation to the degree of inflammation and 2)SOCS3 regulation by miRNA in alveolar-macrophage(AM)-derived extracellular-vesicles(EVs) in bronchoalveolar lavage(BAL). Methods Group A: 35 smokers' lungs [19 with COPD(SC) and 16 without COPD(S)] and 9 of nonsmokers(NS), SOCS3, TNFα in AM and CD8+T-cells were quantified by immunohistochemistry. Group B: In BAL from additional 9SC, 11S and 5NS, AM-EVs expressing SOCS3 (CD14+SOCS3+) and levels of SOCS3-suppressors microRNA(miRNA)-19a-3p and 221-3p in EVs were quantified by flowcytometry and PCR. Results: Percentage of SOCS3+AM was higher in SC[68(6.6-99)%] and S[48(8-100)%] than in NS[9.6(1.9-61)%;p=0.002;p=0.03] and correlated with % of TNFα+AM(r=0.48;p=0.0009) and p=0.0029). In BAL, the CD14+SOCS3+EVs/μl were increased in ;p=0.03] and NS[9(7-21);p=0.003]. Conversely, miRNA-19a-3p and miRNA-221-3p expression were increased in S when compared to vs 3(0.6-8):p=0.03 and 3(0.005-9.6) vs 0.2(0.08-0.7);p=0.05, respectively].The suppressor function of SOCS3 in COPD seems to be overridden by other factors and doesn't follow the animal-model paradigm. Expression of SOCS3 in BAL macrophage-derived EVs might be useful to assess the degree of inflammation and possible progression of COPD. MiRNA downregulation of SOCS3 in smokers without COPD might contribute to the risk of developing cancer in these patients.